Branje pri fantih na Šolskem centru Novo mesto - Jožef-Beg, Jožica (Šolska knjižnica, 2012)
The paper presents the results of a study of reading habits of boys at School centre Novo mesto. Results show that in fiction boys like to read crime stories, and even more adventure stories. Below expectations was reading of learning contents. The choice of reading is most often influenced by recommendations of friends, even though the topic of what is being read is not common among boys. The survey also confirmed the everyday observation in the library that boys in secondary school mostly read home reading books, which is not self-motivated choice. The results are useful for the school library in collection-building activities.
Keywords: bralna pismenost; bralne navade; branje; fantje; mladostniki; raziskave; srednje šole; srednješolci; šolske knjižnice